Potensi Likuifaksi Pada Tanah Pasir Di Atas Tanah Gambut Dengan Variasi Kuari Melalui Uji Model Laboratorium - Ridho Ilahi; Agus Ika Putra; Muhamad Yusa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Indonesia is a country that surrounded by three continental plate. The wave dispersion of this tectonic plate caused the bearing capacity of soil decreased until liquefaction is emerged. Some of area in Sumatera, like Aceh, Padang, Bengkulu and also Pekanbaru is nearby with the boundary fault, which is very risk to get the geotechnical problems caused by liquefaction. This research are using shaking table models have function to determine how big is the effect of sand from varies area and vibration acceleration for liquefaction potential. The vibration acceleration varies is using 0,25 g and 0,32 g. The sand from varies area are came from Danau Bingkuang, Garuda Sakti and Sungai Tonang that has different percentage of fine course, medium course and rough course. According to test results, conclusions that can be determined are that Danau Bingkuang has mostly fine course as 54,27% is get the maximum increasing pore water pressure and maximum soil settlement, and include as the one of most potentially to liquefied.Keywords: Liquefaction, Shaking Table, Quarry, ru Rasio, Embankment.